Organizational Commitment as a Mediating Variable Between Organizational Culture and Civil Servant Performance in Regional Government Institutions - Fatwa Zuhanea (ITB AAS Indonesia Surakarta, 2021)
Civil servant performance in Indonesian regional government remains a persistent policy concern, with organizational culture and commitment identified as critical but understudied determinants. This study investigates the mediating role of organizational commitment between organizational culture and civil servant performance in five Organisasi Perangkat Daerah (OPD) offices in Purbalingga Regency, Central Java. Grounded in Organizational Culture Theory (Schein, 1985) and the Three-Component Commitment Model (Meyer & Allen, 1991), four hypotheses were tested using PLS-SEM with bootstrapping mediation analysis on 152 civil servant respondents. Results confirm that organizational culture significantly affects commitment (β = 0.447, p < 0.001), directly affects performance (β = 0.298, p < 0.001), and that commitment significantly affects performance (β = 0.341, p < 0.001). Organizational commitment partially mediates the culture-performance relationship (indirect β = 0.152, p = 0.001, 95% CI [0.063, 0.248]). The model explains 58.4% of performance variance (R² = 0.584; Q² = 0.312). Total culture-performance effect = 0.450. Findings advance the culture-performance literature and provide evidence-based recommendations for Indonesian regional government HR reform. Keywords: organizational culture; organizational commitment; civil servant performance; regional government; mediation; PLS-SEM; Purbalingga; OPD